2012
DOI: 10.1186/1749-7922-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Complicated intra-abdominal infections in Europe: a comprehensive review of the CIAO study

Abstract: The CIAO Study (“Complicated Intra-Abdominal infection Observational” Study) is a multicenter investigation performed in 68 medical institutions throughout Europe over the course of a 6-month observational period (January-June 2012).Patients with either community-acquired or healthcare-associated complicated intra-abdominal infections (IAIs) were included in the study.2,152 patients with a mean age of 53.8 years (range: 4–98 years) were enrolled in the study. 46.3% of the patients were women and 53.7% were men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
6
13

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 12 publications
6
99
6
13
Order By: Relevance
“…In a recent large Complex IntraAbdominal infection Observational (CIAO) study from Europe [22], the mortality for patients with severe sepsis or septic shock at admission was 32 %, which is comparable to this study.…”
Section: Discussionsupporting
confidence: 73%
“…In a recent large Complex IntraAbdominal infection Observational (CIAO) study from Europe [22], the mortality for patients with severe sepsis or septic shock at admission was 32 %, which is comparable to this study.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, the most common baseline pathogens were Escherichia coli, Klebsiella spp., streptococci, enterococci, and Bacteroides spp., consistent with those associated typically with cIAI, although the recovery of anaerobic pathogens was lower in the present study than in some recent reports (20,21). These pathogens were eradicated at similar rates by both study drugs.…”
Section: Discussioncontrasting
confidence: 33%
“…Moreover, the data coming from the CIAOW study supported effective empirical M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 antimicrobial therapy. An ineffective therapy led to three-fold increase in bacterial resistances [4,23] Our study showed that 44.8% of patients with AC presented with sepsis, 5.8% with severe sepsis and 2.8% with septic shock. Thus, more than half of the patients with AC were critical at presentation, stressing the necessity to initiate timely and effective empirical antibiotic therapy.…”
Section: Discussionmentioning
confidence: 94%